(untitled) - Võ, Tòng Xuân,Võ, Tòng Xuân (Thành phố Hồ Chí Minh, 1998)
The content of this book studied the different enterprises that form the various components of farming activities in farm households, including crops, livestock and aquaculture. Socio-economic analyses of the studied areas were carried out to have a better understanding of the diversity of rice-based farming systems prefered by the local farmers. The farm income in the areas under study was low, indicating the farmers have low technological skills and an inadequate knowledge an natural resource management.
Sinh thái học nông nghiệp,Sinh thái học nông nghiệp
Keywords: Cropping systems,Cropping systems,Farm management; Deltas; Vietnam,Mekong River Delta